2015
DOI: 10.1515/hukin-2015-0034
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Investigation of Impact Loads During the Forward Handspring Vault

Abstract: The purpose of this study was to examine kinematic and kinetic differences in low and high intensity hand support impact loads during a forward handspring vault. A high-speed video camera (500 Hz) and two portable force platforms (500 Hz) were installed on the surface of the vault table. Two-dimensional analyses were conducted on 24 forward handspring vaults performed by 12 senior level, junior Olympic program female gymnasts (16.9 ±1.4 yr; body height 1.60 ±0.1 m; body mass 56.7 ±7.8 kg). Load intensities at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Studies about juniors or beginners categories were found, and the Hetch vault would be a good example of search for any kinematics variable di erences from juniors to seniors, over an identical skill. Another paper advance on the relation between wrist and shoulder angles on junior female handspring vaults 36 . ese comparisons would allow more knowledge about the common gymnast's errors and how to develop the vault technical progressions.…”
Section: Approach Runningmentioning
confidence: 99%
“…Studies about juniors or beginners categories were found, and the Hetch vault would be a good example of search for any kinematics variable di erences from juniors to seniors, over an identical skill. Another paper advance on the relation between wrist and shoulder angles on junior female handspring vaults 36 . ese comparisons would allow more knowledge about the common gymnast's errors and how to develop the vault technical progressions.…”
Section: Approach Runningmentioning
confidence: 99%
“…Wrist positions are known to affect impact force during normal loading [ 50 , 51 ] and Choi et al [ 10 ] observed that peak force on the entire palm increased with increasing wrist angle during a forward fall. Furthermore, Penitente et al [ 52 ] showed that during a gymnastic vault wrist angle affected peak impact force and loading rate. Extending the wrist, results in tension in the skin and soft tissues similar to the observations in the plantar tissues and as a result wrist positions are likely to affect palmar tissue mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Previously force plates have been utilised to measure the landing forces associated with a limited range of gymnastics skills. 2–8 These studies have typically taken place in a controlled laboratory environment and were only conducted on one type of surface (i.e. floor matting).…”
Section: Introductionmentioning
confidence: 99%